Report on maternity insurance (London : Co-operative Printing Society Ltd., 1927)
1927 1927 1920s 16 pages This report was prepared by a Sub-Committee of the British Section of the International Association for Social Progress for the Annual Congress held in Vienna, September, 1927. The Sub-Committee consisted of :- Miss GERTRUDE TUCKWELL, J.P. (Chairman). Miss MARY CARLIN (Transport and General Workers' Union). Mr. J. L. COHEN, M.A. (Cambridge University). Miss DOROTHY EVANS, M.A. (Association of Women Clerks and Secretaries). Lady HALL. Mr. C. M. LLOYD (London School of Economics). Professor D. H. MACGREGOR (Oxford University). Professor CARR SAUNDERS (Liverpool University). Miss CONSTANCE SMITH, O.B.E. Mr. C. F. SHOVE (Cambridge University). Miss DOROTHY ELLIOTT (National Union of General Workers) — Convener. 292/824/1/114